(untitled) (Research, Society and Development, 2025)
The aim of the present study was to identify the main strategies for managing the symptoms of climacteric syndrome in women. A narrative review of the literature was conducted according to the recommendations of the Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) guideline, with studies available in the PubMed database. Only articles published in English or Portuguese, from January 2014 onwards, with experimental or observational design, and populations consisting of women in the climacteric who had received some treatment for climacteric syndrome were included. The diagnosis of climacteric and menopause is clinical and can be complemented by the measurement of follicle-stimulating and luteinizing hormones. The best treatment for vasomotor symptoms is combined and systemic hormone replacement therapy, which is also effective for most symptoms of climacteric syndrome, including genitourinary symptoms, mood and sleep disorders, bone loss and arthralgias. Transdermal hormone therapy is a safe, effective alternative that offers fewer adverse effects than systemic therapy. Isolated genitourinary symptoms can be treated with vaginal estrogen, an option with a good safety and effectiveness profile, or with alternative therapies, including topical prasterone, oral ospemifene, vaginal hyaluronic acid, vaginal lubricants and moisturizers. Climacteric depression is a disorder of endocrine etiology, so hormone replacement therapy offers more satisfactory results than treatment with antidepressants and psychotropic drugs. This review summarized the most recent evidence on the management of climacteric syndrome, presenting effective and safe therapeutic modalities for most patients.